UPAYA GURU PAI DALAM MENGATASI PROBLEMATIKA PEMBELAJARAN RANAH AFEKTIF DI SMAN 1 BAE KUDUS TAHUN 2017 - Zuhri, Achmad (QUALITY, 2017)
This research explains: (1) How problem of teachingIslamic education for affective domain in SMAN 1 Bae Kudus; (2) How theteachers’effort of islamic education for affective domain in SMAN 1 Bae Kudus 2017 Academic Year. This research uses qualitative approach. The study was conducted at SMAN 1 Bae Kudus. Data collection was done by interview, observation, and documentation. The data obtained is analyzed by data reduction measures, data presentation, and conclusions. The researcher collected the data while doing the analysis activity until the concluding. The results obtained in this research indicate that (1) Problematic in learning PAI affective domain at SMAN 1 Bae Kudus include: Students not aware of phenomenon, lack of attention, students less active in responding to the response, students have no confidence in value, The value becomes stable and active in itself, not able to internalize the value, the difficulty of controlling student development, teacher learning evaluation, and the influence of technological progress. (2) PAI teacher's efforts in overcoming problematic in affective learning include:Praying in beginning of learning, giving reprimand and satire, Teacher gives stimulus in the form of story, establishing closeness with student, applying method of discussion, inserting a story, applying method market place, Be a role model for students, transfering religious values intensively, organizing religious activities, provididing motivation, establishing communication between teachers, students, and parents, paying attention and observing learners’ behavior, and controlling the technological progress.